Aromatic porous polymer network membranes for organic solvent nanofiltration under extreme conditions. Issue 31 (22nd November 2019) - Wang, Chenxu; Li, Chenxuan; Rutledge, Evan R. C.; Che, Sai; Lee, Jongbok; Kalin, Alexander J.; Zhang, Caili; Zhou, Hong-Cai; Guo, Zi-Hao; Fang, Lei
Abstract : Organic solvent nanofiltration (OSN) membranes composed of aromatic porous polymer networks are fabricated by in situ cross-linking. They exhibit excellent chemical/structural stability, molecular-sieving selectivity, and high permeability for OSN. Abstract : Aromatic porous polymer networks (PPNs) are promising candidate materials for organic solvent nanofiltration (OSN) membranes, in which molecular-sieving selectivity, high permeability, and chemical/structural stability can be integrated. In this work, aromatic PPN membranes p -PPN, m -PPN and tri -PPN are fabricated by in situ aldol triple condensation cross-linking. These membranes demonstrate high stability, permeability and sharp selectivity in OSN, thanks to the aromatic nature of the backbone, high surface area (up to 1235 m 2 g −1 ), and narrowly distributed pore sizes. They possess a high organic solvent permeability so that a good permeance is achieved despite a thickness of over 100 μm. The molecular weight cut-off and molecular weight retention onset of these membranes are ∼600 g mol −1 and 350 g mol −1, respectively, making it possible to efficiently separate molecules from a complex mixture composed of compounds with only marginally different molecular weights. As a result of the highly stable nature of the aromatic backbones, these PPN membranes show retained structural integrity and OSN performance in the presence of either a strong acid or strong base for over 50 h. The extraordinary stability integrated with excellent permeability and selectivity renders these PPN membranes promising candidates for challenging OSN applications under extreme conditions.